BOOSTING BRAND AWARENESS: LEVERAGING CONTENT MARKETING AND SOCIAL MEDIA FOR GREATER VISIBILITY AND ENGAGEMENT IN PROPERTY BUSINESS - Panjaitan, Raya; Purba, Cindy Braveta (UNIKA Santo Thomas, 2020)
This study examines the effects of content marketing and social media on brand awareness for PT. Peta Property Indonesia in Medan, employing a quantitative approach with descriptive statistics. It analyzes how these digital strategies enhance the company's visibility and consumer engagement. The research finds that content marketing and social media significantly increase brand awareness, attributed to the unique, engaging, and informative nature of the company's content. This includes well-presented property information, which is easily accessible and understandable to consumers. By strategically showcasing a range of properties, including new developments and secondary market listings, the content effectively informs consumers about available options. Additionally, incorporating interactive elements like quizzes and games into the content boosts engagement and fosters a two-way communication channel. The study concludes that effective content marketing and social media use are crucial for enhancing brand visibility and establishing a stronger connection with the target audience for PT. Peta Property Indonesia.